2023
DOI: 10.3390/diagnostics13152471
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis and Classification of Fetal Health Status from a Fetal Cardiotocography Dataset Using Ensemble Learning

Abstract: (1) Background: According to the World Health Organization (WHO), 6.3 million intrauterine fetal deaths occur every year. The most common method of diagnosing perinatal death and taking early precautions for maternal and fetal health is a nonstress test (NST). Data on the fetal heart rate and uterus contractions from an NST device are interpreted based on a trace printer’s output, allowing for a diagnosis of fetal health to be made by an expert. (2) Methods: in this study, a predictive method based on ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The importance of ensemble learning techniques is further highlighted in a research paper concluded by [11], which achieved remarkable accuracy levels above 99.5%. This approach significantly improves prediction performance, demonstrating the potential of combining multiple classifiers in fetal health diagnostics.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The importance of ensemble learning techniques is further highlighted in a research paper concluded by [11], which achieved remarkable accuracy levels above 99.5%. This approach significantly improves prediction performance, demonstrating the potential of combining multiple classifiers in fetal health diagnostics.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Equation (1) below succinctly illustrates the precise methods used in the normalization and standardization process. In this equation, '𝑥' represents the original input values, and '𝑥′' denotes the transformed values, reflecting the enhanced, range-bound, and standardized data [17].…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Kuzu et al proposed a batch learning-based prediction method for the classification of fetal health (normal, suspicious, pathological) using fetal heart rate acceleration obtained from a cardiotocography (CTG) dataset and NST tests in their study (22). In this research, they developed binary and multiclass classification models using LR, RF, and extreme gradient boosting (XGBoost) algorithms, and applied these models to the UCI dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was observed that 22 features were used in two studies and 23 features were used in two studies using cross validation (CV) along with accuracy, precision, recall and F 1 score metrics. Kuzu et al achieved 100% accuracy as a result of their experiments using the polynomial expansion (PE) function for feature extraction along with CV, entropy and normalisation (22). Das et al on the other hand, achieved 99.91% accuracy by using standard dimensionality reduction algorithms such as PCA, correlation-based feature subset selection, Chi-squared feature selection, MinMax, and CV methods (64).…”
Section: Artificial Intelligence In Fetal Healthmentioning
confidence: 99%